Modeling of Exhaust (Waste) Water in the Extraction of Hydrogen Sulfide Black Sea - Tsitskhishvili, Marat S.; Shaptoshvili, Alexander E. (Journals of Georgian Geophysical Society, 2017)
Numerical models, “basic control parameters”, Simulation for the case of waste water discharge into the river, model parameters, MacCormack's predictor-corrector. Due to selection of more realistic parameter values in the numerical schemes, the use of Kolmogorov's approximation of turbulent diffusion obtained practically relevant values of pollution fields for the different placement of sources of pollution. The paper presents the results of calculations of pollution fields.